Microbial Decontamination of Onion by Corona Discharge Air Plasma during Cold Storage - Eun Ha Chang; Yeoung Seuk Bae; Il Sheob Shin; Hyun Jin Choi; Ji Hyun Lee; Ji Weon Choi (Journal of Food Quality)
Corona discharge air plasma (CDAP) is a nonthermal decontamination technology which is generating antimicrobial agents such as photons, electrons, positively and negatively charged ions, atoms, and free radicals. We investigated the effect of a corona discharge under atmospheric pressure on the sterilization of postharvest fungal pathogens on onion. The main antimicrobial reactive substance generated by CDAP was O3. The active species such as nitric oxide (NO) and nitric dioxide (NO2) were nearly detected in this experiment. CDAP treatment revealed different isolation frequencies depending on postharvest pathogens from diseased onions, showing less isolation frequency of Fusarium spp. and Alternaria sp. than that of Botrytis spp. when compared with untreatment onions during 10-month cold storage. CDAP treatment at 2∼2.6 ppm of O3 slightly stimulated the mycelial growth of Alternaria sp., while the treatment at 20∼24 ppm of O3 gradually inhibited mycelial growth by treatment time. However, Botrytis sp. showed different patterns of mycelial growth with CDAP treatment. Less than 4 hours’ treatment of CDAP slightly inhibited the mycelial growth of Botrytis sp., while 8 hours’ treatment of CDAP slightly stimulated the mycelial growth of Botrytis sp. not depending on the concentration of O3. The inhibitory effect of CDAP on the conidial germination of Alternaria sp. and Botrytis sp. was examined with treatment time and intensity of CDAP. The conidial germination of Alternaria sp. treated with CDAP at the concentration of 13.7∼14.4 ppm of O3 was strongly inhibited by time, showing y = 2.66x2 − 85.139x + 4.88 and R2 = 0.98. When the conidia of Alternaria sp. were exposed for 2 hours with varying plasma O3 concentration, the conidial germination was strongly inhibited as the concentration of O3 increases, showing y = −0.09x2 + 6.905x − 0.764 and R2 = 0.95. The conidia of Botrytis sp. also showed similar patterns to CDAP. The inhibitory effect of CDAP on the germination of postharvest pathogens depends on treatment time and O3 concentration.